Risk preferences and the low-carbon agricultural technology adoption: Evidence from rice production in China - Hui MAO; Yu-rong QUAN; Yong FU (Journal of Integrative Agriculture, 2023)
Climate change which is mainly caused by carbon emissions is a global problem affecting the economic development and well-being of human society. Low-carbon agriculture is of particular significance in slowing down global warming and reaching the goal of “carbon peak and carbon neutrality”. Therefore, taking straw incorporation as an example, this paper aims to investigate the impact of risk preferences on farmers’ low-carbon agricultural technology (LCAT) adoption. Based on a two-phase micro-survey data of 1 038 rice farmers in Jiangsu, Jiangxi, and Hunan provinces, this paper uses experimental economics methods to measure farmers’ risk aversion and loss aversion to obtain the real risk preferences information of the farmers. We also explore the data to examine the actual LCAT adoption behavior of farmers. The results revealed that both risk aversion and loss aversion significantly inhibit farmers’ LCAT adoption: more risk-averse or more loss-averse farmers are less likely to adopt LCAT. It is further found that crop insurance, farm scale and governmental regulations can alleviate the negative impact of risk aversion and loss aversion on farmers’ LCAT adoption. Therefore, we propose that local governments need to promote low-carbon agricultural development by propagating the benefits of LCAT, extending crop insurance, promoting appropriate scale operations, and strengthening governmental regulations to promote farmers’ LCAT adoption.